National Lesbian Health Care Survey, 1984-1985 - Bradford, Judith B. ([Verlag nicht ermittelbar], 1989)
This survey was stimulated by recognition of the need for accurate normative information about the health and health care needs of lesbians in the United States. The purpose of the survey was to provide comprehensive data regarding health care needs of lesbians, to identify gaps in service, and to make recommendations about training and service provision. Information is available on mental health experiences and concerns, mothering, physical abuses, sexual attacks, experiences with discrimination, substance abuse, and community and social life.